ANALISIS PERJANJIAN PENGIKATAN JUAL BELI TANAH DAPAT MENJADI AKTA JUAL BELI TANPA KEHADIRAN PENJUAL (STUDI KASUS: PUTUSAN PENGADILAN NEGERI SURABAYA NOMOR 1292/PDT.G/2019/PN.SBY) - Meilivia Winandra; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2021)
The sale and purchase of land are one of the legal acts of transfer of land rights. The parties can make a sale and purchase agreement as a preliminary agreement before the deed of sale and purchase is made in the context of land registration. In the case studied, there was a problem seller refusing to make a deed of sale and purchase, even though the buyer had paid in full for the object. So that raises problems related to how a sale and purchase agreement can become a deediofisale iand ipurchase iwithoutithe ipresence iofithe iselleriin ithe icase iDecision iofithe iSurabaya iDistrictiCourt iNumberi1292/Pdt.G/2019/PN.Sby. iThe imethod iused iisinormative ilegaliresearch. The results show that the sale and purchase agreement was made privately deed and there were no provisions regarding the power to sell. Likewise, the court's decision stipulates that the sale and purchase are legal and valuable based on the sale and purchase agreement and decide to make a deed of sale and purchase by Deed Official even though without the presence of the seller is legal certainty that an action can be carried out. Preferably, the making of the sale and purchase agreement made by Notary which is an authentic deed with perfect evidentiary power and the government provides legal socialization to the public regarding the sale and purchase of land to increase knowledge and understanding of the importance of making a sale and purchase agreement with an authentic deed.